ARCHIVES – A MIRROR OF HISTORY - Dilfuza Joraeva Jangirovna (Scholar Express Journal, 2022)
In this article, as we begin to educate today's youth in the spirit of patriotism and love for the values of the nation, we need to know the history of our ancestors in depth. For this, it is said that we need to know the fate of the nation we belong to, the amount of creativity and creativity carried out by our people in different periods, and most importantly, we need to know historical facts.
Keywords: National Archives Fund; Central State; Central Archives